Decomposing niche components reveals simultaneous effects of opposite deterministic processes structuring alpine small mammal assembly - Song, Wen-Yu; Onditi, Kenneth Otieno; Li, Xue-You; Chen, Zhong-Zheng; He, Shui-Wang; Li, Quan; Jiang, Xue-Long (Frontiers in Ecology and Evolution, 2023)
Our knowledge of community assembly dynamics under multiple stressors is limited because of opposite niche-based processes, i.e., limiting similarity and habitat filtering could simultaneously occur, masking the overall patterns. Alpine biomes provide the ideal systems to explore the influences of co-occurrence processes as these communities usually face multiple stresses such as resources limitation and habitat constraints. However, the community assembly processes of mammals in alpine areas have hardly been exclusively studied. Here, we aimed to address how different processes structured small mammal communities at the tree line transition zone, which represents one of the most distinct vegetation boundaries separating alpine from montane habitats. We compiled a regional dataset including species list, phylogeny, and functional traits from field collections across 18 mountains of southwest China and complemented them with data from published sources. The traits were decomposed into different niche components to determine the respective effects of specific stressors. Phylogenetic and functional diversity indices representing evolutionary history, trait space, and pairwise species distance were calculated and compared with null expectations. Linear mixed-effect models were constructed to assess the increasing or decreasing tendencies of diversity values against increasing elevation. The results showed that phylogenetic and functional richness were strongly correlated with species richness, unlike the distance-based indices which were uncorrelated with species richness. There was no evidence found to support non-random phylogenetic or overall trait patterns. However, the resource acquisition niche tended to be more overdispersed (positive slopes), while the habitat affinity niche tended to be more clustered (negative slopes) as habitats became less productive and less vegetated. We conclude that limiting similarity and habitat filtering simultaneously structure small mammal communities in alpine areas. Altogether, the present study provides vital insights into the complexity of co-occurring assembly processes by niche decomposition, and highlights the importance of considering different diversity dimensions when assessing community structure.